2012
DOI: 10.1016/j.rbmo.2011.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophins (BDNF and NGF) in follicular fluid of women with different infertility diagnoses

Abstract: Brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF) are intra-ovarian signalling peptides that are important in follicle development and oocyte maturation. In the ovary, neurotrophin expression is regulated by gonadotrophins. Therefore, this study postulates that aetiology of infertility will affect follicular-fluid BDNF and NGF concentrations. Follicular fluid from the first follicle aspirated from 190 infertile women attending a university-affiliated fertility programme (McMaster Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Interestingly, the levels of NGF in follicular fluid derived from women with polycystic ovary syndrome (PCOS) were lower compared with the control group, but BDNF concentrations did not vary (Buyuk & Seifer 2008), suggesting an effect potentially attributable to the different aetiologies of infertility. This notion is supported by a recent study demonstrating that follicular fluid BDNF concentrations were only higher in women diagnosed with unexplained infertility following ovulation induction, while no relationship could be established between levels of BDNF or NGF in women with a history of either endometriosis or PCOS compared to controls (Sadeu et al 2012). It should be noted that this particular study included only a small number of participants, the stage of disease was not factored into the measurements and there may be differences in ovulation induction procedures that vary between facilities that could explain the differences reported across different studies.…”
Section: Potential Clinical Significancementioning
confidence: 84%
“…Interestingly, the levels of NGF in follicular fluid derived from women with polycystic ovary syndrome (PCOS) were lower compared with the control group, but BDNF concentrations did not vary (Buyuk & Seifer 2008), suggesting an effect potentially attributable to the different aetiologies of infertility. This notion is supported by a recent study demonstrating that follicular fluid BDNF concentrations were only higher in women diagnosed with unexplained infertility following ovulation induction, while no relationship could be established between levels of BDNF or NGF in women with a history of either endometriosis or PCOS compared to controls (Sadeu et al 2012). It should be noted that this particular study included only a small number of participants, the stage of disease was not factored into the measurements and there may be differences in ovulation induction procedures that vary between facilities that could explain the differences reported across different studies.…”
Section: Potential Clinical Significancementioning
confidence: 84%
“…Also in mammalian species, several studies documented that BDNF is a physiological regulator of normal follicle maturation (Pan and Auersperg, 1998;Seifer et al, 2002) and may function in both early and later stages of folliculogenesis (Linher-Melville and Li, 2013), although with specific differences in the localization within the follicle. Indeed, in the ovary of humans, BDNF was detected in the follicular fluid (Seifer et al, 2002;Seifer et al, 2006;Sadeu et al, 2012), in the follicular cells, such as granulosa cells (Zhao et al, 2011) and cumulus cells, and in the oocyte (Anderson et al, 2002). Furthermore, BDNF was reported in the granulosa cells of primordial and primary follicles of mouse (Paredes et al, 2004), and in the cumulus and granulosa cells of mature follicles in mouse (Kawamura et al, 2005), cow (Martins da Silva et al, 2005), and pig (Lee et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Many reports had demonstrated that BNDF is a paracrine/autocrine regulator that is required for follicular growth and oocyte development in the mammalian ovary [4][7], [28], [29]. Recently it has been proved that BDNF is involved in not only stress-related mood disorder [13], but also some human reproductive diseases, such as polycystic ovary syndrome [30] and infertility [31]. Our data showed for the first time that BDNF in ovary may be involved in the impaired oocytes developments induced by chronic stress.…”
Section: Discussionmentioning
confidence: 99%